Amlodipine increases risk of primary open-angle glaucoma - Lehrer, Steven; Rheinstein, Peter H. (Clinical hypertension, 2024)
The use of calcium channel blockers is associated with primary open-angle glaucoma (POAG) in a statistically meaningful but minor way. In general, those who had received calcium channel blocker medication were at a 23% increased risk of developing glaucoma in comparison to those who had never taken the antihypertensive drugs. We wished to confirm this association and examine POAG genes that might be involved, since the genetics has not yet been analyzed. We used MedWatch and UK Biobank data to evaluate the effects of amlodipine on POAG and intraocular pressure (IOP). We analyzed three POAG-associated single-nucleotide polymorphisms: rs9913911, an intron variant in growth arrest-specific 7 (GAS7), one of the genes that influences IOP; rs944801, an intron variant within CDKN2B-AS1, and rs2093210, an intron variant within SIX6, known to be associated with vertical cup-disc ratio, an important optic nerve head parameter that is often used to define or diagnose glaucoma. Amlodipine use in MedWatch doubled the prevalence of POAG, from 0.0805 to 0.177%, a small but significant increase. Multivariate analysis by logistic regression of UK Biobank data revealed that POAG risk was significantly increased with age, male sex, major alleles of rs9913911 (GAS7) and rs944801 (CDKN2B-AS1), and minor allele of rs2093210 (SIX6). Amlodipine increased POAG risk by 16.1% (P = 0.032). Amlodipine has not been associated with increased IOP. We confirmed this lack of association and in addition found that GAS7, associated with IOP, was not associated with POAG risk and amlodipine. But CDKN2B-AS1 and SIX6, POAG genes not associated with IOP, were associated with POAG and amlodipine. Amlodipine, a frequently prescribed drug and first line treatment for hypertension, has a potentially hazardous relationship with POAG. Knowledge of this link can guide the prescribing of alternate drugs for hypertensive individuals who have glaucoma or are at risk for it. Diuretics and β-blockers are not associated with POAG or increased IOP and could be substituted for amlodipine in hypertensive patients at risk POAG. None.